ANALYSIS OF STUDENT ERRORS IN SOLVING PROBLEMS OF DEVICE AND ROOT FORM BASED ON NOLTING THEORY IN CLASS IX PONPES AL-IKHLAS ADDARY MTs DDI TAKKALASI - Sitti Rahma; Rustan Efendy; Hasmiah Herawaty (Prodi. Pendidikan Matematika, FKIP, Universitas Riau, 2022)
Mathematics is continuous learning with previous materials. Students consider this lesson difficult, especially during the Covid-19 period, because they cannot study normally. This causes students to have difficulty learning mathematics and making mistakes in solving problems. This research was conducted to analyze students' errors in solving problems of powers and roots. The research method used is descriptive research with a qualitative approach. A written test consisting of 4 numbers becomes a research instrument. The percentage of student errors based on the Nolting Theory consists of carelessness errors that are 3.45%, conceptual errors that are 19.59%, application errors of 3.69%, and errors in determining the answer results are 12.56%. Result determination error has a higher percentage than other types of errors. These errors occur because students do not understand the material, including basic mathematics. Lack of understanding of the concept of powers and roots.